2007
DOI: 10.1111/j.1365-3040.2007.01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel pathogen‐responsive cis‐elements and their binding proteins in the promoter of OsWRKY13, a gene regulating rice disease resistance

Abstract: The WRKY transcription factor superfamily controls diverse developmental and physiological processes in plants. However, little is known about the factors that directly regulate the function of WRKY genes. In this study, we identified cis-acting elements and their binding proteins of rice OsWRKY13, a gene that plays a pivotal role in disease resistance against bacterial and fungal pathogens. Two novel pathogen-responsive cis-elements, PRE2 and PRE4, were characterized from the promoter region of OsWRKY13. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 42 publications
4
79
0
Order By: Relevance
“…Six distinct proteins, including OsWRKY13, were identified in a yeast one-hybrid screen that bind to functionally important cis-regulatory DNA elements within the rice OsWRKY13 promoter (Cai et al, 2008). Similar screens employing the AtWRKY53 promoter led to the identification of a MAP kinase kinase kinase (MEKK1).…”
Section: Regulation Via Other Tfs and Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six distinct proteins, including OsWRKY13, were identified in a yeast one-hybrid screen that bind to functionally important cis-regulatory DNA elements within the rice OsWRKY13 promoter (Cai et al, 2008). Similar screens employing the AtWRKY53 promoter led to the identification of a MAP kinase kinase kinase (MEKK1).…”
Section: Regulation Via Other Tfs and Proteinsmentioning
confidence: 99%
“…Members of this family contain at least one conserved DNA-binding region, designated the WRKY domain, comprising the highly conserved WRKYGQK peptide sequence and a zinc finger motif (CX 4-7 CX 22-23 HXH/C). This domain generally binds to the DNA element termed the W box (C/TTGACT/C), although alternative binding sites have been identified (Sun et al, 2003;Cai et al, 2008;Ciolkowski et al, 2008;van Verk et al, 2008). WRKY family members are divided into three groups based on the number of WRKY domains and certain features of the zinc finger-like motifs (Eulgem et al, 2000).…”
Section: The Wrky Factorsmentioning
confidence: 99%
“…However, a recent study demonstrated that the TGAC core sequence is sufficient to be targeted for binding by the AtWRKY28 protein (van Verk et al, 2011). Some other WRKY transcription factors, such as rice (Oryza sativa) OsWRKY13 and Hordeum vulgare HvWRKY46, can bind to non-W-box sequences (Cai et al, 2008;Mangelsen et al, 2008). Gel-shift experiments also suggest that different groups of WRKY transcription factors show different binding site preferences to recognize TTGACC and TTGACT (Ciolkowski et al, 2008).…”
mentioning
confidence: 99%
“…Our understanding of the roles of plant tubby genes is very limited. TLPs are believed to participate in the ABA signaling pathway in Arabidopsis (Lai et al, 2004;Cai et al, 2008) and the OsTLP family is involved in host-pathogen interactions in rice (Kou et al, 2009).…”
Section: Discussionmentioning
confidence: 99%